Policy use of well-being metrics Describing countries' experiences - Exton, Carrie (OECD Statistics Working Papers, 2018)
The last decade has seen major advances in the measurement of well-being in national statistics - but what are governments doing to incorporate these metrics and frameworks into policy decision making? This paper describes the progress made in many countries on measuring well-being at a national level, and the mechanisms being developed to mainstream both concepts and evidence on well-being into policy settings. In all cases, countries are adopting a multidimensional approach to the measurement of well-being, and several initiatives have been informed by extensive public consultation processes. For seven countries, detailed case studies in the Annex describe the development and implementation of policy mechanisms for integrating well-being evidence: Ecuador, France, Italy, New Zealand, Scotland, Sweden, and the United Kingdom. The paper finds that well-being evidence is applied at several different stages of the policy cycle, from strategic analysis and prioritization to evaluations of policy interventions. In most cases these initiatives are only a few years old, and institutional support will be vital for the durability of these mechanisms over time and through different political cycles